(untitled) (FUDMA JOURNAL OF SCIENCES, 2020)
The study involved the analysis of some selected heavy metals in drinking water consumed within Katsina Metropolis. The water samples were collected from Ajiwa dam raw water, taps, wells, boreholes, and sachet waters and the concentration of heavy metals (Cd, Pb, Cr, Co, and Ni), was determined using Atomic Absorption Spectrophotometer (AAS). The results obtained from the water analysis indicate that cadmium was not found in all the water samples. The concentrations range for lead were (6.222-109.63)µg/L with maximum concentration value of 109.63 µg/L in Ajiwa dam raw water, above the World Health Organization (WHO) limit, nickel (0.72-6.99)µg/L with maximum concentration value of 6.99 µg/L in borehole water, within WHO limit, chromium (36-72)µg/L with maximum concentration value of 72 µg/L in well water, above WHO limit, cobalt (4.758-9.516) µg/L with maximum concentration value of 9.516 µg/L in well water, within WHO limit. The results indicate that most of the concentrations of the heavy metals determined were within the WHO limit, except for chromium in well water which may arises from the Government activities of money recycling and incineration of old bank notes which does not affect other water sources in the area and lead in Ajiwa dam raw water which was further removed through water treatment processes. Moreover, the Analysis of Variance (ANOVA) indicate no significant difference in the means of the heavy metals concentrations in all the water samples analyzed, and this may be due to the same physicochemical factors and limited industrial activities in the study area